2017
DOI: 10.1007/s11004-017-9701-2
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-outcrop Visualization of Borehole Images and Core Scans

Abstract: A pseudo-outcrop visualization is demonstrated for borehole and full-diameter rock core images to augment the ubiquitous unwrapped cylinder view and thereby to assist non-specialist interpreters. The pseudo-outcrop visualization is equivalent to a nonlinear projection of the image from borehole to earth frame of reference that creates a solid volume sliced longitudinally to reveal two or more faces in which the orientations of geological features indicate what is observed in the subsurface. A proxy for grain s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…It proves effective in revealing the morphology of stratigraphic structures, layer properties, and relationships between different geological layers. Mirkes et al [14] demonstrated a pseudo-outcrop visualization method for borehole and full-diameter rock core images, aiming to augment the ubiquitous unwrapped cylinder view and assist non-specialist interpreters. The pseudo-outcrop visualization is equivalent to a nonlinear projection of the image from the borehole to an earth frame of reference, creating a solid volume sliced longitudinally to reveal two or more faces.…”
Section: Related Workmentioning
confidence: 99%
“…It proves effective in revealing the morphology of stratigraphic structures, layer properties, and relationships between different geological layers. Mirkes et al [14] demonstrated a pseudo-outcrop visualization method for borehole and full-diameter rock core images, aiming to augment the ubiquitous unwrapped cylinder view and assist non-specialist interpreters. The pseudo-outcrop visualization is equivalent to a nonlinear projection of the image from the borehole to an earth frame of reference, creating a solid volume sliced longitudinally to reveal two or more faces.…”
Section: Related Workmentioning
confidence: 99%
“…Javier et al [19] employed drones to create highly accurate and high-resolution 3D models for identifying and interpreting ancient Roman gold mining sites in Northwestern Spain, revealing areas such as excavation sites, canals, reservoirs, and drainage channels. Mirkes et al [20] proposed a semantic segmentation method for rock outcrops that leads to the detection and segmentation of various geometric features, including fractures, faults, and sedimentary layers. Zhang et al [21] state that most existing semantic segmentation methods are based on FCNs, which replace the fully connected layer with fully convolutional layers for pixel-level prediction.…”
Section: Related Studiesmentioning
confidence: 99%
“…where ( ) ij f v is the average value on each slice; fij is the value of each point on the slice; mij is the number of points. To judge whether the points in the image are from the same slice, we utilize the method of Mirkes [49]. This method can quickly search for the points from the same slice in a Cartesian coordinate system.…”
Section: Optimal Sinusoid Extractionmentioning
confidence: 99%